The determinants of financing of coal-fired power plants - Makhafola, Tebatjo (University of the Witwatersrand, Johannesburg, 2024)
Coal-fired power stations have been the key driver of energy generation for many decades in many economies. Generating electricity using coal is regarded as reliable because coal-fired power plants can provide a continuous power supply. However, as reliable as theyare, coal-fired power plants pose environmental challenges, from greenhouse gas emissions to air pollution. This research paper aims to investigate factors other than environmental concerns, that determine the funding of coal-fired power plants (research objective one), to investigate the economic effect of changes in the funding of coal-fired power plants (research objective 2) as well as to investigate whether there is a causality between funding for coal-fired power plants and renewable energy output (research objective 3). The panel data ordinary least square regression model was used for investigating the determinants of coal-fired power plants and for investigating the economic impact of changes in funding of coal-fired power plants. The Dumitrescu-Hurlin Panel causality analysis was performed to investigate the causality between coal funding and renewable energy output. Regarding the determinants of coal funding, the results show that interest rate, unemployment rate, access to electricity, GDP per capita, and inflation have a significant influence on funding for coal-fired power plants. However, financial depth and emissions do not have a significant influence on funding for coal-fired power plants. Funding for coal-fired power plants is found to have a significant influence on economic growth. The study further found that there exists a unidirectional causality relationship between funding for coal-fired power plants and renewable energy output, flowing from funding for coal-fired power plants to renewable energy output. As the results show that coal fundings tend to decrease as the economy grows, these findings imply that investors in coal-fired power plants and coal-producing companies should consider diversifying their investment portfolio to other alternative energy sources that have growth potential, like renewable energy. Based on the causality results, the implication is that policymakers may be making decisions concerning funding for coal-fired power plants in line with those decisions made to achieve sustainability through renewable energy.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Finance and Investment to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: financing of coal-fired power plants; UCTD; SDG-8: Decent work and economic growth